The Effects of Proprioceptive Neuromuscular Facilitation and Static Stretching Performed at Various Intensities on Hamstring Flexibility - Woo-taek Lim (Korean Research Society of Physical Therapy, 2020)
Background: To prevent or reduce the risk of strain injury, various approaches, including stretching techniques are currently being used. The effect of proprioceptive neuromuscular facilitation (PNF) and static stretching on flexibility has been demonstrated; however, it is not clear which one is superior. Objects: This study aimed to evaluate the differences between the effects of PNF and static stretching performed at various intensities on muscle flexibility. Methods: The maximum voluntary isometric contraction (MVIC) of the hamstrings using the PNF stretching technique was performed in the P100 group, while 70% of the MVIC was performed in the P70 group. The MVIC value obtained during the PNF stretching in both groups was used as a reference for setting the intensity of static stretching. Static stretching was performed at 130% (S130), 100% (S100), and 70% of the MVIC (S70). The active knee extension (AKE) values, defined as the knee flexion angle were measured before stretching (baseline), immediately after stretching (post), and at 3 minutes, 6 minutes, and 15 minutes. Results: PNF stretching produce a greater improvement in flexibility compared with static stretching. Specifically, the AKE was significantly higher in the S100 and S70 groups than in the P100 group at Post. In the comparison of AKE over time in each group, the AKE at Post showed a significant decrease compared to the value at Baseline in the S130 group; however, no significant difference was observed at 6 minutes while a significant increase was noted at 15 minutes. Conclusion: This study found that PNF stretching is more effective than static stretching with respect to increasing and maintaining the flexibility of muscles. In addition, the increase in flexibility at maximal intensity was similar to that observed at submaximal intensity during both PNF and static stretching.